STRUCTURE AND DYNAMICS OF VEGETATION COVER UNDER LARGE SCALE MAPPING GEOBOTANICAL - R. S. Kuznetsova (Юг России: экология, развитие, 2014)
Short description of formation of large scale geobotanical mapping is given. Geobotanical works on mapping of structure and dynamics of vegetation cover are presented. The prospects of geobotanical mapping are discussed.